2016
DOI: 10.1111/ggi.12853
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the effect of exercise interventions between prefrail older adults and older adults without frailty: A pilot study

Abstract: These results suggest that we can expect similar interventional effects for prefrail older adults and robust older adults. It is important that a frail status be prevented in prefrail older adults by using an exercise intervention. Further studies are required to determine the different effects of exercise intervention on prefrail status compared with frailty status in community-dwelling older adults. Geriatr Gerontol Int 2017; 17: 1265-1269.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…In general, our results are comparable with those of previous studies. However, contrary 11 to other studies, Takano et al showed that the implementation of 4-month exercise interventions did not significantly affect frailty status (38).…”
Section: Discussionmentioning
confidence: 75%
“…In general, our results are comparable with those of previous studies. However, contrary 11 to other studies, Takano et al showed that the implementation of 4-month exercise interventions did not significantly affect frailty status (38).…”
Section: Discussionmentioning
confidence: 75%
“…Similar to a previous study (Uchmanowicz et al, 2020), frailty is associated with the increase in the hazard of hospitalization across clinical contexts in CHF patients. The guidelines of CHF management indicated that exercise could improve physical function and quality of life, and decrease rehospitalization and mortality (Takano et al, 2017). The participants with exercise (≥30 minutes one time) at least three times a week show a low prevalence of frailty in our findings.…”
Section: Discussionmentioning
confidence: 99%
“…2 Nutrition or protein supplementation regimes described in studies included appropriate dietary emphasis on daily milk, eggs, tuna, chicken, plant-based protein, or, where preferred, 2 × 200 mL of formula per day (containing 25 g protein, 400 kcal energy, 9.4 g essential amino acids, and 400 mL water). 34 Several studies found that participation rates in physical exercise activities remained as high as 90%, [66][67][68] though some dipped to 50%. 54 A differentiator appears to have been the level of periodic encouragement to continue participation by practising medical professionals.…”
Section: Implications For Research and Practicementioning
confidence: 99%